Configuring Irishness through coaching films: Peil (1962) and Christy Ring (1964). Issue 1 (2nd January 2016) - Crosson, Seán
Abstract: The sports coaching film has a long history, dating from at least 1932 with the production of Paulette McDonagh's How I Play Cricket which featured the legendary Don Bradman. However, coaching films dedicated to indigenous Irish sport, or Gaelic games, are a more recent development, emerging in the late 1950s. This article considers two such films – Peil (Louis Marcus, 1962) and Christy Ring (Louis Marcus, 1964) – dedicated to Gaelic football and hurling, respectively, and produced by the Irish-language cultural organisation Gael Linn. The principal concern in undertaking this examination is to identify the process by which these films configure Irishness, not just through the depictions of the indigenous sports featured but also through the manner in which these depictions are framed. In "configuring Irishness", the article examines in particular how these films articulate Irish identity and its constituent properties, particularly in terms of language, geography, politics and religion, thereby "coaching" viewers in Irishness itself, its features, and Ireland's political and moral leaders.